1985
DOI: 10.1002/ijc.2910350210
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating mononuclear cells in human breast carcinoma: Predominance of T4+ monocytic cells in the tumor stroma

Abstract: Frozen sections of 52 breast carcinomas were examined for the presence and nature of a leukocytic infiltrate. The number of "common leukocyte (T200-) antigen"-bearing cells was remarkably high in the stromal compartment of the carcinomas, whereas the tumor foci themselves were usually infiltrated only sparsely. Approximately 80% of these T200+ stromal cells carried the myelomonocyte lineage-associated antigens M-M522 and 63D3 and exhibited "non-specific esterase" activity. More than 2/3 of the stromal monocyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 27 publications
4
19
1
Order By: Relevance
“…The variability of staining for HLA-DR on the breast carcinoma cells reported here is consistent with previous immunohistochemical data published by Natali et al (1983), Whitwell et al (1984 and Gottlinger et al (1985). The use of paraffinembedded tissue sections which provide superior preservation of morphologic features, rather than frozen sections employed by the investigators referred to above, permitted more definitive analysis, a factor that becomes critical in the attempt to discriminate between a wholly negative tissue or one which contains some scattered positive carcinoma cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The variability of staining for HLA-DR on the breast carcinoma cells reported here is consistent with previous immunohistochemical data published by Natali et al (1983), Whitwell et al (1984 and Gottlinger et al (1985). The use of paraffinembedded tissue sections which provide superior preservation of morphologic features, rather than frozen sections employed by the investigators referred to above, permitted more definitive analysis, a factor that becomes critical in the attempt to discriminate between a wholly negative tissue or one which contains some scattered positive carcinoma cells.…”
Section: Discussionsupporting
confidence: 89%
“…Among the reports concerning the expression of HLA-DR antigens on epithelia-derived neoplasms, breast tumours represent perhaps the most conflicting group of malignancies with the observed percentage of positive tumours ranging from zero (Hurliman & Saraga, 1985) or only a few (Bhan & Des Marais, 1983) up to 100% (Bernard et al, 1984) with some intermediate values found by Natali et al ( ), Whitwell et al (1984 and Gottlinger et al (1985). To illustrate the extent of discrepancies published by various authors, Hurliman and Saraga (1985) found none of 61 breast carcinomas positive while Bernard et al (1984) reported that all 19 mammary carcinomas examined expressed HLA-DR antigens, despite the fact that a similar immunohistochemical technique and the same monoclonal antibody (OK Ia from Ortho) to HLA-DR were used by both groups of investigators.…”
mentioning
confidence: 99%
“…Furthermore, there was a trend for lower tumor grade in those tumors that expressed DR in the absence of a substantial T-cell infiltration, suggesting DR expression in the absence of T cell-derived cytokines may result from molecular changes during malignant transformation. Overall, in concordance with earlier studies, 19,20 DR was significantly associated with T-cell infiltration, supporting the hypothesis that DR is induced on tumor cells in response to the cytokine milieu of the tumor microenvironment.…”
Section: Hla-dr ϩ Tumor Cells Discordantly Express Hla-drb Allelic Prsupporting
confidence: 91%
“…13,14 However, the significance of these findings is controversial as some studies suggested DR expression on breast tumor cells is associated with favorable prognostic indicators such as well-differentiated tumors 15,16 and hormone receptor expression, 17 while others found no effect. 13,18 Similarly, tumor cell DR was positively associated with T-cell infiltration in some studies 19,20 and unrelated in others. 16,21 Interpretation of the above studies may have been hampered by the fact that generic and not allelic DR expression was examined.…”
mentioning
confidence: 92%
“…These influences are mainly due to cells of the defence system (Boheim et al, 1987;Kopper & Lapis, 1985;Zeromski et al, 1986;Kabawat et al, 1983). In vitro assays have demonstrated a significant role for T cells, natural killer (NK) and lymphokine-activated killer (LAK) cells in killing and lysing of neoplastic cells (Patek & Collins, 1988; Strohme et al, 1987;Whiteside et al, 1988;Vinzenz & Micksche, 1987;Gottlinger et al, 1985). Activated macrophages (Me), also, can bind to and destroy neoplastic cells in vitro and in vivo (Fidler & Schroit, 1984;Fidler & Schroit, 1988;Kopper & Lapis, 1985).…”
mentioning
confidence: 99%